THE EFFECTIVENESS OF STEM BASED LEARNING METHODS IN IMPROVING PROBLEM SOLVING SKILLS IN DYNAMIC ELECTRICAL MATERIAL - Rudi Purwanto (Formad English Foundation NTB Jakarta, 2025)
STEM-based learning (Science, Technology, Engineering, and Mathematics) has been widely recognized as an effective educational approach in the 21st century to enhance students' critical thinking and problem-solving skills. This study aims to examine the effectiveness of STEM-based learning compared to conventional methods in improving students' problem-solving skills in dynamic electricity material. The research employed a quasi-experimental design involving two groups: an experimental group that received STEM-based learning and a control group that followed conventional learning methods. Data were collected through pretest and posttest assessments, classroom observations, and teacher interviews. The results showed that students in the STEM-based learning group achieved a significantly higher posttest score (M = 82.6, SD = 6.7) compared to the control group (M = 73.2, SD = 7.5). The N-Gain analysis indicated a medium-high category improvement (0.67) in the experimental group, while the control group showed a medium category improvement (0.48). Furthermore, the independent t-test confirmed a statistically significant difference in problem-solving skill enhancement between the two groups (t = 3.21, p < 0.05). Observational data also revealed that STEM-based learning promoted higher student engagement (M = 4.2 on a 5-point scale) compared to conventional methods (M = 3.5). These findings suggest that STEM-based learning is not only more effective in improving students’ problem-solving skills but also in increasing their engagement in the learning process. Thus, the implementation of STEM-based learning can serve as an alternative strategy to develop 21st-century competencies, particularly in physics education.